Age Dependent Progression of Multiple Epiphyseal Dysplasia and Pseudoachondroplasia Due to Heterozygous Mutations in COMP Gene - El-Lababidi, Nabil; Zikánová, Marie; Baxová, Alice; Nosková, Lenka; Leiská, Alena; Lambert, Lukáš; Honzík, Tomáš; Zeman, Jiří (Prague Medical Report, 2020)
Dominantly inherited mutations in COMP gene encoding cartilage oligomeric matrix protein may cause two dwarfing skeletal dysplasias, milder multiple epiphyseal dysplasia (MED) and more severe pseudoachondroplasia (PSACH). We studied the phenotype and X-rays of 11 patients from 5 unrelated families with different COMP mutations. Whole exome and/or Sangers sequencing were used for molecular analyses. Four to ten X-ray images of hands hips, knees or spine were available for each patient for retrospective analyses. Eight patients with MED have mutation c.1220G>A and 3 children with PSACH mutations c.1359C>A, c.1336G>A, or the novel mutation c.1126G>T in COMP. Progressive failure in growth developed in all patients from early childhood and resulted in short stature < 3rd percentile in 7 patients and very short stature < 1st percentile in four. Most patients had joint pain since childhood, severe stiffness in shoulders and elbows but increased mobility in wrists. Six children had bowlegs and two had knock knees. In all patients, X-rays of hands, hips and knees showed progressive, age-dependent skeletal involvement more pronounced in the epiphyses of long rather than short tubular bones. Anterior elongation and biconvex configuration of vertebral bodies were more conspicuous for kids. Six children had correction of knees and two adults had hip replacement. Skeletal and joint impairment in patients with MED and PSACH due to COMP mutation start in early childhood. Although the clinical severity is mutation and age dependent, many symptoms represent a continuous phenotypic spectrum between both diseases. Most patients may benefit from orthopaedic surgeries.
Keywords: mutace; retrospektivní studie; Child, Preschool; Matrilin Proteins; matriliny; Achondroplasia; osteochondrodysplazie; Child; Cartilage Oligomeric Matrix Protein; dítě; Adult; dospělí; Severity of Illness Index; předškolní dítě; Osteochondrodysplasias; lidé; achondroplazie; Humans; chrupavkový oligomerní matrixový protein; stupeň závažnosti nemoci; Mutation; Retrospective Studies